A Blockchain-Based Vehicle Rental System Using Ethereum - OOI, POH QIN; RAMLI, SOFIA NAJWA (Applied Information Technology And Computer Science, 2026)
In this digital age, vehicle rental platforms have become one of the important methods for people to rent a car temporarily for short-term travel at anytime and anywhere. However, traditional centralized vehicle rental platforms possess several problems including high intermediary fees and risk of disputation over rental agreements. The project aims to develop a partially decentralized blockchain-based vehicle rental system using Ethereum to provide a transparent, immutable rental service with minimal third-party involvement. Agile methodology is used to develop this system. Blockchain is implemented in the system to store smart contracts and transaction information to ensure immutability and tamper-proof agreements. The developed system will foster trust among users by ensuring tamper-proof agreements, efficient payments, and reduced costs. Future work can be done to integrate advanced features such as integrating common payment methods and launch on Mininet to further enhance the system's utility.